2011
DOI: 10.1097/pec.0b013e318209f076
|View full text |Cite
|
Sign up to set email alerts
|

False Elevation of Carboxyhemoglobin

Abstract: Carboxyhemoglobin serum level, in infants, may be falsely elevated due to the fetal hemoglobin interfering with standard methods of analysis. Knowledge of the false elevation using standard spectrophotometric methods of COHb in clinically well-appearing infants can decrease unnecessary oxygen therapy and monitoring time in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…Further investigation revealed that her falsely elevated carboxyhemoglobin level was due to interference of fetal hemoglobin in spectrophotometric measurements of carboxyhemoglobin [5]. The exact duration of exposure was unknown.…”
Section: Case Reportmentioning
confidence: 98%
“…Further investigation revealed that her falsely elevated carboxyhemoglobin level was due to interference of fetal hemoglobin in spectrophotometric measurements of carboxyhemoglobin [5]. The exact duration of exposure was unknown.…”
Section: Case Reportmentioning
confidence: 98%
“…La mesure par spectrophotom etrie est populaire car il s'agit d'une m ethode simple, pr ecise, rapide et accessible [6]. Cependant, certains articles soulignent que la mesure spectrophotom etrique de la HbCO peutêtre sujette aux interf erences caus ees par l'h emoglobine foetale (HbF) [7,8]. L'h emoglobine foetale est structurellement similaire a l'h emoglobine adulte (HbA) mais peut se lier a l'oxyg ene avec une meilleure affinit e [2].…”
Section: Introductionunclassified
“…[7] et Mehrotra et al[8] rapportent que la mesure spectrophotom etrique de la HbCO est faussement elev ee par la pr esence de l'HbF, cr eant des faux positifs aussi elev es que 8% avec le CO-oxym etre. Zwart et al[13] et Variend et al[14] rapportent que dans la m ethode propos ee par Katsumata et al[4], la r eduction du sang avec le dithionite de sodium elimine l'interf erence de l'HbF, et donc devrait eliminer le biais positif lors de l'utilisation du spectrophotom etre.…”
unclassified
“…The spectrophotometric measurement is very popular because it is simple, accurate, rapid and accessible 6 . However, it is reported that spectrophotometric measurement of HbCO can be subject to interferences from fetal hemoglobin (HbF) 7,8 . Fetal hemoglobin is structurally similar to adult hemoglobin (HbA) but can bind oxygen with greater affinity 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on this topic yield contradictory results. Vreman et al 7 and Mehrotra et al 8 report that spectrophotometric measurement of HbCO is falsely elevated by the presence of HbF, giving false positive results up to 8% when using a CO-oximeter. Zwart et al 13 and Variend et al 14 report that in the method proposed by Katsumata et al 4 , reduction of blood with sodium dithionite eliminates the interference of HbF, and thus should not give positive bias when using a basic spectrophotometer.…”
Section: Introductionmentioning
confidence: 99%